FASILITASI PENGAWAS SEKOLAH DALAM BERBAGI PRAKTIK BAIK PADA KEPALA SEKOLAH DI LUWU UTARA - Harry Yulianto (Nindikayla Institute, 2023)
School supervisor as a part of education was help improvement the quality of education. School supervisors need to disseminate best practices to provide inspiration for schools. This activity aims to facilitate school supervisors to plan mentoring programs for headmaster on a regular basis. The activity was carried out offline (face to face) and was attended by school supervisors at the junior and senior high school levels in North Luwu. Methods of implementing activities: training and facilitation. Data analysis was using descriptive statistics. The results of the activities: (1) the school supervisor's facilitation activities were carried out well; (2) the results of the training indicated the participants had a high level of ability in absorbing knowledge and implementing basic concepts regarding the role of school supervisors for share best practices; and (3) the results of facilitation have a positive impact on school supervisors in designing mentoring activities for school principals